1983
DOI: 10.1002/bit.260250805
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation, chelation, and the availability of metals as nutrients in anaerobic digestion. I. Methodology

Abstract: A methodology has been developed for the quantitative assessments of the individual effects of precipitation and chelation of metal ions in an anaerobic digester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 13 publications
2
55
1
2
Order By: Relevance
“…These metals are, therefore, only bioavailable if the wastewater micro-organisms have a stronger affinity for the metal than the complexing agent (Callander and Barford, 1983). Previous researchers have concluded that precipitated metals are not readily bioavailable to micro-organisms (Aquino and Stuckey, 2007;Callander and Barford, 1983;Gonzalez-Gil et al, 2002;Hoban and van den Berg, 1979;Mosey et al, 1971;Pfeffer and White, 1964;Zandvoort et al, 2006), which corresponds to their resistance to extraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These metals are, therefore, only bioavailable if the wastewater micro-organisms have a stronger affinity for the metal than the complexing agent (Callander and Barford, 1983). Previous researchers have concluded that precipitated metals are not readily bioavailable to micro-organisms (Aquino and Stuckey, 2007;Callander and Barford, 1983;Gonzalez-Gil et al, 2002;Hoban and van den Berg, 1979;Mosey et al, 1971;Pfeffer and White, 1964;Zandvoort et al, 2006), which corresponds to their resistance to extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is known to be an essential metal for all micro-organisms (Hughes and Poole, 1989) and has been reported to increase AS microbial activity when supplemented to nutrient-deficient systems (Carter and McKinney, 1973;Derco et al, 1998). Iron is particularly important for efficient anaerobic metabolism (Callander and Barford, 1983;Hoban and van den Berg, 1979;Pfeffer and White, 1964) and has been found to increase biogas production significantly when supplemented to anaerobic digesters with low bioavailable iron concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that pH influences the solubility of P and micronutrients; e.g., raising the pH moves the chemical equilibrium toward the formation of dissociated phosphate ion, which facilitates the precipitation of such ion as insoluble Ca and Mg phosphates. Some other concerns, such as the binding form of other elements, as Fe, may be regulated by AD [11]. Also, during AD, the fraction of dissolved P becomes mineralized and it becomes associated with suspended solids [12].…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…This is likely due to absence of the competition between methanogen and SRB because the reactors fed with sulfate recorded only 67%-70% of COD to methane conversion with the feeding of 200-333 mg-S/L sulfate [42]. There are two possible reasons for the low activity in the presence of high concentration sulfide: (1) reduction of bioavailability of metal ions precipitated as insoluble salts of Co, Ni and Fe [43]; and (2) toxicity of sulfide to microorganism [41]. The equilibrium calculation suggested that in 200 and 500 mg-S/L sulfide-containing influent wastewaters, over 99.7% of Fe, Ni, Co were present in the forms of solid (inert sulfide salt) at 35 °C and pH 7.8.…”
Section: Effect Of High Concentration Of Sulfide On Performance Of Upmentioning
confidence: 99%